A GENERALIZATION OF A JACOBSON’S COMMUTATIVITY THEOREM (Journal of Sciences, Islamic Republic of Iran)
In this paper we study the structure and the commutativity of a ring R, in which for each x,y ? R, there exist two integers depending on x,y such that [x,y]k equals x n or y n.